Edukasi Keuangan dan Financial Check Up UMKM - Yendrawati, Reni; Assidiqy, Jamaluddin (Rahmatan Lil 'Alamin Journal of Community Services, 2026)
MSMEs (Micro, Small and Medium Enterprises) are one of the pillars of the Indonesian economy. To strengthen these efforts, a strong contract basis is needed in Islamic business as well as management in terms of financial health. The method of implementing this socialization is carried out by delivering material, direct discussions, and searching data through the internet as the basis for preparing empowerment materials. The results obtained are that to strengthen the sharia basis in business for MSME actors in Canden Hamlet, Ngargosari Village, Samigaluh District, Kulon Progo. It is necessary to understand the basic principles of contracts in business and to maximize profits for MSMEs, a Financial Check-up is needed. Knowing financial health will form motivation to improve and know the important role of saving for the needs of the community in Canden Hamlet.